DESIGN OF SUNDANESE LANGUAGE INTRODUCTION LEARNING APPLICATIONS - Sekar Larasati; Egi Badar Sambani; Yuda Purnama Putra; Susanto; Gilda intan permadi (Journal of Multimedia Technology and Applied Software, 2025)
The declining interest in learning the Sundanese language, especially among younger generations, is influenced by the limited availability of engaging and easily accessible learning media. This study aims to develop an Android-based application for introducing basic Sundanese as an interactive and flexible alternative learning tool. The development process adopts the Multimedia Development Life Cycle (MDLC), which includes concept, design, material collecting, assembly, testing, and distribution stages. The application provides fundamental Sundanese learning materials such as numbers, greetings, self-introduction, and non-verbal language, complemented by a quiz feature to evaluate user comprehension. Blackbox testing indicates that all application features function properly. Usability testing involving 30 respondents using a Likert scale obtained a feasibility score of 85.5%, categorized as highly feasible. The average quiz score of 96 further demonstrates the application's effectiveness in enhancing users' understanding of the material. Therefore, this learning application is considered suitable as a supporting tool for learning the Sundanese language and has the potential to increase local language literacy in the community.